2019
DOI: 10.1002/htj.21448
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of second‐grade fluid flow past a stretching sheet

Abstract: The present numerical study reports the chemically reacting boundary layer flow of a magnetohydrodynamic second-grade fluid past a stretching sheet under the influence of internal heat generation or absorption with work done due to deformation in the presence of a porous medium. To distinguish the non-Newtonian behaviour of the second-grade fluid with those of Newtonian fluids, a very popularly known second-grade fluid flow model is used. The fourth order momentum equation with four appropriate boundary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Thus, to solve this system of PDE's, we first transformed the system of coupled PDE's to a set of simplified nonlinear ordinary differential equations (ODEs) with the help of the appropriate similarity transformations. Finally, the reduced first order ODEs are solved by using Runge‐Kutta fourth order integration scheme with shooting technique (RK‐SM) 31‐34,42‐51 and the bvp4c matlab function 31‐34,52 . Thus, to achieve the above‐mentioned purpose, the following similarity transformations 9‐14 are suitably used.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to solve this system of PDE's, we first transformed the system of coupled PDE's to a set of simplified nonlinear ordinary differential equations (ODEs) with the help of the appropriate similarity transformations. Finally, the reduced first order ODEs are solved by using Runge‐Kutta fourth order integration scheme with shooting technique (RK‐SM) 31‐34,42‐51 and the bvp4c matlab function 31‐34,52 . Thus, to achieve the above‐mentioned purpose, the following similarity transformations 9‐14 are suitably used.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Clearly, it is observed that the governing Equations (21) to (23) with conditions Equations (24) to (26) are not amenable to analytical schemes. Hence, in the present paper, an attempt has been made to overcome this difficulty by using RK‐SM 31‐34,42‐51 and bvp4c techniques 31‐34,52 . Thus, before applying the RK‐SM technique, the nonlinear coupled ODE's Equations (21) to (23) are decomposed into a system of first order ODE's and the reduced equations are as follows.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Also, at time tfalse′>0, the temperature of the cylinder at rfalse′=R, has elevated to Tw, whereas at r=0, it has an adiabatic phase which causes the temperature gradient and the buoyancy force accruing to the motion. As the flow is depending on the coordinate r and time t, the governing momentum and thermal energy equations of the transient free convective flow of a second‐grade fluid in a vertical cylinder using the Boussinesq's approximations are given as 9,35 υ()2urtrue′2+1rtrue′ur+α1ρ()3utrtrue′2+1rtrue′2utrut+gβ(TT0)=0, κρCp()2Trtrue′2+1rtrue′TrTt=0.…”
Section: Mathematical Formulationsmentioning
confidence: 99%
“…Reddy et al 33 have examined natural convection and entropy generation on the viscoelastic polymeric fluid flow over a vertical plate. Furthermore, the entropy generation for the transient flow of a second‐grade fluid through a vertical cylinder has been investigated by Reddy et al 34 Basha et al 35 have analyzed chemically reacting second‐grade fluid flow on the stretching sheet. Furthermore, the exact solutions of the transient flow problems in a circular cylinder have been obtained by the researchers 36,37 …”
Section: Introductionmentioning
confidence: 99%
“…However, it is noticed from the available literature that, the Equations to are not easily amenable to any of the direct methods. Therefore, the coupled Equations to with Equations and are simplified by utilizing the standard RK‐SM and bvp4c method . However, the RK‐SM begins by discretising the coupled higher nonlinear ODEs into a system of first order ODEs.…”
Section: Numerical Solution Proceduresmentioning
confidence: 99%